THE SYNTACTICAL AND LEXICAL PECULIARITIES OF SENSORICS IN “HAIR” BY W. FAULKNER - Khalilovich, Suleymanov Timur (PT. Antis International Publisher, 2024)
The article includes an explanation of the ways of sensory perception of reality by the characters of W. Faulkner's short story “Hair”, and it gives a description of the concepts associated with sensorics. It also demonstrates the features of W. Faulkner's legendary style. In addition, the article analyzes the synthesis of visual, auditory, tactile, olfactory imagery by the characters of “Hair”.